Business opportunities in Egypt and Israel infrastructure, transportation and utility. - Chia, Darren Yeow Ghee. (2008)
This dissertation studies the infrastructure support of Egypt and Israel, highlights the implications and explores the business opportunities for potential business partners and investors.